METODE PENYAMPAIAN DALAM PENDIDIKAN ISLAM - Al Qifari, Abudzar (Inspiratif Pendidikan, 2020)
The basics of disseminating Islamic education consist of religious and bio-psychological basics. Bio-psychological basic is divided into three types, namely; biological, psychological and social basics. The classical method that was carried out during the Abbasiyah dynasty led the society realized the importance of the science development and community needs. The teaching methods used at that time were oral, memorizing, and writing. Oral method included dictation, lecture, qira’ah and discussion. The methods that could be applied in schools/madrasah, namely: lecture, discussion, experimental, demonstration, assignment, socio-drama, drill method, group-work, question and answer, and project methods. Besides, the most important was the exemplary and the habituation methods.